Perlindungan Hukum terhadap Anak dalam Nikah Siri - Muhammad Jazil Rifqi (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2020)
Married couples must meet religious and state law. In Islamic law, marriages must be fulfilled, the harmony of the marriage, the bride and groom, prospective guardians, marriage, two people, consent and Kabul, while state law, needs to be added validity, marriage, must be in accordance with applicable law. However, not a few marriages in areas that carry out their marriages are only based on religious law and customary law, without involving Marriage Registrar to improve this marriage by considering siri marriages that increase returns to desired husbands and children. Civil rights are not guaranteed at the time of marriage to a siri marriage because the child will not obtain citizenship status, and the child only has a civil relationship with the mother and related family, which basically requires the cost of child care.